1985
DOI: 10.1159/000171688
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Tuberculosis: Report of a Case and Review of the Literature

Abstract: Tuberculosis of the perianal region is a proportionally rare and misdiagnosed disease. We present a patient who was operated upon 5 times for persistent perianal fistula and recurrent abscess formation. Only a specific animal test and biopsy confirmed the diagnosis. The literature is reviewed and the differential diagnosis as well as the need to investigate cases of resistant perianal pathology are stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
1
7
0
4
Order By: Relevance
“…Anal fistula is the most frequent symptom of anorectal TB (80∼91% of cases) (7)(8)(9) and anal TB is commonly seen in men (4:1 ratio) and …”
Section: Resultsmentioning
confidence: 99%
“…Anal fistula is the most frequent symptom of anorectal TB (80∼91% of cases) (7)(8)(9) and anal TB is commonly seen in men (4:1 ratio) and …”
Section: Resultsmentioning
confidence: 99%
“…[14] The anoperineal area is rarely affected with TB and represents less than 1% of all intestinal TB. [15], [16], [17], [18] In US, population groups at particular risk for intestinal tuberculosis are immigrants, AIDS, urban poor, the Indians on reservations. [10] Marshal JB has reported that almost 15-20% of intestinal TB have active lung TB at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…[14] In addition, in miliary TB, haematogenous or lymphatic spread considered as another source of intestinal TB. [9], [16] However, many other reports have described that gastrointestinal TB happens concomitant with or secondary to pulmonary TB [15], [17], [18], [19] which might be manifested thereafter or might not. [10] Nevertheless, gastrointestinal TB including Intestinal and anoperineal may develop by reactivation of the latent focus and pulmonary tuberculosis may not present.…”
Section: Discussionmentioning
confidence: 99%
“…La prévalence des localisations périanales n'est pas connue, mais elles représenteraient 0,3 à 6 % des fistules anales [2]. Il existe un long délai entre les manifestations cliniques initiales et le diagnostic [3]. Dans notre cas, ce délai a été de huit mois.…”
Section: Réponses Et Commentairesunclassified